SUNDANESE PHONOLOGICAL INTERFERENCE OF THE RECITATION OF SURA AL-FATIHA OF THE HOLY QURAN - Tatang, Tatang; Hayati, Cucu (Jurnal Pendidikan Bahasa dan Sastra, 2019)
Culture is one of elements that affect a person's proficiency of foreign languages. Sundanese phonological structure is different from Arabic. Therefore, it is difficult for some Sundanese people to pronounce Arabic. For example, Sundanese tends to face difficulties in reciting the verses of the Holy Quran. The Holy Quran is the Muslims’ holy book that is written in Arabic. The recitation of the Holy Quran should be in accordance with the Arabic phonology. In fact, Some Sundanese make irregularities or interference during reciting the Suras (chapters) of the Holy Quran. This study aims to reveal the phonological interference experienced by Sundanese speakers in reciting the Sura Al-Fatiha of the Holy Quran. The data in this study covers the recitations of the Sura Al-Fatiha. The data is retrieved through observation, recording, and interviews with some Sundanese people that live around the UPI Campus. The study concludes that there are five phonological interference phenomena in the pronunciation of the Hijā’ī (Arabic Alphabet) during the recitation of Sura Al-Fatiha. They are lenition, sound reinforcement, unusual sound changes, the voice addition, and assimilation. Some factors cause such interferences. They cover the influence of the Sundanese vocabulary and Arab phonemes that do not exist in the phonology of the Sundanese language.